Effect of co-ingestion of amino acids with rice on glycaemic and insulinaemic response. Issue 11 (30th September 2015) - Soong, Yean Yean; Lim, Joseph; Sun, Lijuan; Henry, Christiani Jeyakumar
Abstract: Consumption of high glycaemic index (GI) and glycaemic response (GR) food such as white rice has been implicated in the development of type 2 diabetes. Previous studies have reported the ability of individual amino acids to reduce GR of carbohydrate-rich foods. Because of the bitter flavour of amino acids, they have rarely been used to reduce GR. We now report the use of a palatable, preformed amino acid mixture in the form of essence of chicken. In all, sixteen healthy male Chinese were served 68 or 136 ml amino acid mixture together with rice, or 15 or 30 min before consumption of white rice. Postprandial blood glucose and plasma insulin concentrations were measured at fasting and every 15 min after consumption of the meal until 60 min after the consumption of the white rice. Subsequent blood samples were taken at 30-min intervals until 210 min. The co-ingestion of 68 ml of amino acid mixture with white rice produced the best results in reducing the peak blood glucose and GR of white rice without increasing the insulinaemic response. It is postulated that amino acid mixtures prime β -cell insulin secretion and peripheral tissue uptake of glucose. The use of ready-to-drink amino acid mixtures may be a useful strategy for lowering the high-GI rice diets consumed in Asia.